2011
DOI: 10.1124/mol.110.069583
|View full text |Cite
|
Sign up to set email alerts
|

A Cation-π Interaction at a Phenylalanine Residue in the Glycine Receptor Binding Site Is Conserved for Different Agonists

Abstract: Cation-interactions have been demonstrated to play a major role in agonist-binding in Cys-loop receptors. However, neither the aromatic amino acid contributing to this interaction nor its location is conserved among Cys-loop receptors. Likewise, it is not clear how many different agonists of a given receptor form a cation-interaction or, if they do, whether it is with the same aromatic amino acid as the major physiological agonist. We demonstrated previously that Phe159 in the glycine receptor (GlyR) ␣1 subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 46 publications
(74 reference statements)
6
40
0
Order By: Relevance
“…The slope for residue 206 (0.13) is slightly higher than for 254 (0.11), which could indicate that the cation-π interaction is stronger at the 254 site. Our recent study of cation-π interactions of different agonists in glycine receptors suggests that the exact orientation of the cationic moiety influences the strength of a cation-π interaction at a given site (Pless et al, 2011), consistent with a computational study which demonstrated that the exact orientation of the aromatic residue and the cation are crucial for a strong cation-π interaction (Gallivan and Dougherty, 2000). …”
Section: Discussionsupporting
confidence: 85%
“…The slope for residue 206 (0.13) is slightly higher than for 254 (0.11), which could indicate that the cation-π interaction is stronger at the 254 site. Our recent study of cation-π interactions of different agonists in glycine receptors suggests that the exact orientation of the cationic moiety influences the strength of a cation-π interaction at a given site (Pless et al, 2011), consistent with a computational study which demonstrated that the exact orientation of the aromatic residue and the cation are crucial for a strong cation-π interaction (Gallivan and Dougherty, 2000). …”
Section: Discussionsupporting
confidence: 85%
“…1C). These residues are in agreement with the data obtained from functional and mutagenesis studies regarding agonist binding (Rajendra et al, 1995;Laube et al, 2002;Pless et al, 2011;Yu et al, 2014).…”
Section: General Structure Of Cys-loop Receptorssupporting
confidence: 81%
“…Moreover, this approach is helpful, because it allows for the straightforward comparison of the present study with other previously characterized cation-pi systems through the relative slope of the plot. For instance, viewing our results in light of previously confirmed cation-pi interactions in ligand-gated channels where, although the drug/receptor ratio is different (1:1 for anti-arrhythmic drugs and sodium channels; at least 2:1 for pentameric ligand-gated channels and their agonists), the slopes of the cation-pi plots for lidocaine and mexiletine ( − 0.08 and − 0.06, respectively) are similar to those observed for activation of the nicotinic acetylcholine receptor with acetylcholine ( − 0.11) 35 and the activation of the glycine receptor with β-alanine and taurine ( − 0.12 and − 0.09, respectively) 36 .…”
Section: Resultsmentioning
confidence: 52%